Analisis Peran dan Peluang Technopreneurship di Era Revolusi Industri 4.0 dalam Perspektif Ilmu Pendidikan Kewirausahaan - Sri Mulyati (Departement of Mathematics Education, 2022)
In a descriptive way, this study will provide an overview of entrepreneurship and small and medium enterprises using technology. From all points of view, both motivation, ownership, managerial, employment, and so on Technopreneurship can be educated through the world of education as a world of transformation, namely the science of developing entrepreneurship by using technology as a basis for entrepreneurship. Technopreneurship comes from an invention and innovation. The fact is that before the new normal phase, the increase and use of internet technology has indeed made a myriad of conveniences in human life. Until now, especially in the field of trade in goods and services, many consumers and producers have benefited from the emergence of increasingly complex technological developments. This is in line with the needs in the Industrial Revolution 4.0. The future business perspective must be built from a foundation of mastery of technology and then transformed into a business basis (technology-business-based). The research method uses a conceptual descriptive analysis research method which is sourced from secondary data by using literature studies through entrepreneur literature using a technological basis from various media books and journals.